ALKALINE PHOSPHATASE ENZYMES ACTIVITY IN FRESHWATER FISH Channa punctatus EXPOSED TO CHLORPYRIFOS - REVATHI, B.; LAKSHMANAN, S.; AJITHKUMAR, M.; HEMA, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Chlorpyrifos is commonly used insecticide for agricultural and nonagricultural purpose in Tamilnadu. The alkaline phosphatase enzymes activity of gill, liver, kidney, brain and muscle of treated fish Channa punctatus was studied after exposure to sub lethal concentration of chlorpyrifos. There is significant decrease in alkaline phosphatase enzymes activity of gill, liver, kidney, brain and muscle in treated group compared with control fish. The efficiency of chlorpyrifos in the destruction of total alkaline phosphate enzymes content was evaluated by Langmuir and Freundlich isotherm models in relations of Qm and Kf. The spontaneity of the reaction in between chlorpyrifos and fish alkaline phosphate enzymes was determined by Gibb’s free energy equation. The present analysis reports the metabolic dysfunction in response to pesticide toxicity in the fish.